The Analysis of Production Factors and Income of Potato Farming - Budi Setiawan, Avi; Inayati, Chusna (Universitas Negeri Semarang, 2020)
Banjarnegara Regency has the highest potato productivity in Central Java Province. However, not all sub-districts in Banjarnegara produce potatoes, there are only four from 20 Sub-districts. One of them is Batur sub-district. This study chose Batur sub-district because it is the largest producer of potatoes from three Sub-districts in Banjarnegara. Unfortunately, the huge amount of production did not affect the fluctuation which tended to decrease. Through this problems, this study aimed to determine the determinant of production and income analysis of potato farming in Batur sub-district. The sample of this study were 97 people in Batur sub-district selected from calculation by using the Slovin formula. Then, the variables of this study were land area (X1), labor (X2), fertilizer (X3), pesticides (X4) and production yields (Y). To collect the data, this study used questionnaires, interviews and documentation. The data were analyzed by using multiple regression analysis and R / C ratio analysis. The results showed that the variables of land area, fertilizer, and pesticides had positive and significant influence on potato production. Meanwhile, the labor variable was insignificant by having the return to scale value of 0.89. Further, the average income of potato farming was Rp 7,099,612 / planting season with R / C ratio of 1.77. Shortly, potato farming in Batur sub-district is profitable to continue.